2005
DOI: 10.1002/jcop.20075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a national indicated preventive intervention program

Abstract: For the most part, information concerning the effects of preventive interventions for youth at risk is more anecdotal than scientific. There have been few longitudinal studies with adequate control groups. Conceptual, methodological, and theoretical complexities limit our ability to assess program effectiveness adequately. As scientific knowledge in secondary prevention (selective, indicated prevention) is scarce, the Federal Office of Public Health in Switzerland established the national program, supra-f (Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…These men had commonly failed to complete service and were less educated than the other men in the intervention group. This finding was in line with previous studies, according to which young people with the greatest problems and the fewest coping skills do not seek help (Carlton & Deane, 2000;Deane et al, 2001;Hüsler et al, 2005). Studies by Ciarrochi and colleagues have shown that adolescents who were low in emotional awareness, and who were poor at identifying, describing and managing their emotions, were the least likely to seek help from professional or non-professional sources and had the highest intention of refusing help from everyone.…”
Section: Figure 1 Mean Sum Score Of Accumulated Psychosocial Problemssupporting
confidence: 93%
See 2 more Smart Citations
“…These men had commonly failed to complete service and were less educated than the other men in the intervention group. This finding was in line with previous studies, according to which young people with the greatest problems and the fewest coping skills do not seek help (Carlton & Deane, 2000;Deane et al, 2001;Hüsler et al, 2005). Studies by Ciarrochi and colleagues have shown that adolescents who were low in emotional awareness, and who were poor at identifying, describing and managing their emotions, were the least likely to seek help from professional or non-professional sources and had the highest intention of refusing help from everyone.…”
Section: Figure 1 Mean Sum Score Of Accumulated Psychosocial Problemssupporting
confidence: 93%
“…Less attention has been paid to the success of adhering to interventions and programmes that provide support for young people. Hüsler et al (2005) found that the higher the risk related to psychosocial problems, the lower the success rate of integration following the intervention among young people. According to a meta-analysis (Kampman, 2004) patients most associated with non-adherence to psychiatric treatment are young males with a history of substance abuse, low social functioning or unemployment, or with limited insight into their illness.…”
Section: F E a T U R Ementioning
confidence: 96%
See 1 more Smart Citation
“…In existing studies and literature, these are often suggested to be the key factors of effective preventive and promotive programmes for adolescents (Durlak & Wells, 1997;Greenberg et al, 2001Greenberg et al, , 2003Catalano et al, 2002Catalano et al, , 2004Flay, 2002;Biddle et al, 2004;Rickwood et al, 2005). It is also important to consider the developmental stage and tasks of the adolescent (Hodgson et al, 1996;Hüsler et al, 2005;O'Connell et al, 2009). Dryfoos has (1990) suggested, for example, that enhancement of early education and prevention of school failure should be given high priority, not only by those who want to lower the drop-out rate, but also by those interested in preventing substance abuse and conduct disorders.…”
Section: Figure 2 the Life Situation Of Clients At The End Of The Supmentioning
confidence: 99%
“…Participants were recruited from the supra-f study (Hüsler, Werlen & Blakeney, 2005), a national secondary prevention programme initiated by the Federal Office of Public Health in Switzerland. Youths in the age range 11-20 years taking part in the programme in 12 different centres in the French-and German-speaking parts of Switzerland are included in supra-f.…”
Section: Participantsmentioning
confidence: 99%